Elevating the Growth and Production of Asparagus Beans Through the Use of Coffee Grounds and Rice Husk Ash - Mardhiana, Mardhiana; Jenni, Jenni; Adiwena, Muh. (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2025)
Asparagus beans (Vigna unguiculata subsp. Sesquipedalis) have high economic and nutritional potential, but their yield has declined due to suboptimal land fertility. Inorganic fertilizers pose adverse influence on the environment, so more eco-friendly organic materials, such as coffee grounds and rice husk ash are necessary. This study aims to evaluate the effect of coffee grounds and rice husk ash on the growth and production of asparagus beans. It was conducted in the experimental garden of the Faculty of Agriculture, Universitas Borneo, Tarakan City, using a Randomized Block Design (RBD) with five treatments: no coffee grounds and rice husk ash (P0), 1.5 ton/ha of coffee grounds (P1), 4 ton/ha of rice husk ash (P2), 0.75 ton/ha of coffee grounds + 2.0 ton/ha of rice husk ash (P3), and 1.5 ton/ha of coffee grounds + 4 ton/ha of rice husk ash (P4). The results corroborated that using 1.5 ton/ha of coffee grounds (P1) yields the highest outcome with respect to plant height (113.4 cm), the number of leaves (38 strands), the number of pods to the control (4 pieces), the length of the pods (4.01 cm), and the weight of the pods (140.65 g), compared to other treatments and control. Coffee grounds are proven a more effective material than its combination with rice husk ash in elevating the growth and yield of asparagus beans in red-yellow podzolic soil.